2010
DOI: 10.1111/j.1755-3768.2009.01718.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic retinal vessel response to flicker in age-related macular degeneration patients before and after vascular endothelial growth factor inhibitor injection

Abstract: . Purpose:  Retinal vessel responses to flickering light are different in various systemic and ocular diseases and can be improved after successful therapy. We investigated retinal vessel response to flickering light in age‐related macular degeneration (AMD) patients before and after treatment with a single intravitreal bevacizumab (Avastin®) injection. Methods:  In 10 patients with exudative AMD [age: median (1.quartile; 3.quartile) 76.0 (73.5; 80.0) years], retinal vessel reactions were examined by Dynamic V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 35 publications
3
21
0
Order By: Relevance
“…Whereas Sato and colleagues (Sato et al 2006) did not find a difference in mean blood velocity, arterial diameter or mean blood flow rate in patients with AMD, a more recent study demonstrates reduced blood flow velocities in patients with AMD compared with healthy subjects (Burgansky-Eliash et al 2014). Human studies investigating flicker-induced vasodilation in patients with AMD have also reported an altered flicker response in subjects with advanced AMD (Lanzl et al 2011). Whether these results can be attributed to vascular dysregulation leading to a decreased sensitivity of the retina to the flicker stimulus or to neuronal dysfunction remains unclear.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Whereas Sato and colleagues (Sato et al 2006) did not find a difference in mean blood velocity, arterial diameter or mean blood flow rate in patients with AMD, a more recent study demonstrates reduced blood flow velocities in patients with AMD compared with healthy subjects (Burgansky-Eliash et al 2014). Human studies investigating flicker-induced vasodilation in patients with AMD have also reported an altered flicker response in subjects with advanced AMD (Lanzl et al 2011). Whether these results can be attributed to vascular dysregulation leading to a decreased sensitivity of the retina to the flicker stimulus or to neuronal dysfunction remains unclear.…”
Section: Discussionmentioning
confidence: 95%
“…A recent study, however, reports that retinal blood flow velocities are reduced in patients with AMD (Burgansky-Eliash et al 2014). In addition, it has been shown that flickering light-induced vasodilation of retinal vessels is altered in patients with advanced AMD (Lanzl et al 2011). Based on these findings, one might hypothesize that also retinal blood flow regulation may be compromised in patients with AMD.…”
Section: Introductionmentioning
confidence: 96%
“…Whereas Sato and colleagues (Sato et al 2006) did not find a difference in mean blood velocity, arterial diameter or mean blood flow rate in patients with AMD, a more recent study demonstrates reduced blood flow velocities in patients with AMD compared with healthy subjects (Burgansky-Eliash et al 2014). Human studies investigating flicker-induced vasodilation in patients with AMD have also reported an altered flicker response in subjects with advanced AMD (Lanzl et al 2011). Whether these results can be attributed to vascular dysregulation leading to a decreased sensitivity of the retina to the flicker stimulus or to neuronal dysfunction remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study, however, reports that retinal blood flow velocities are reduced in patients with AMD (Burgansky-Eliash et al 2014). In addition, it has been shown that flickering light-induced vasodilation of retinal vessels is altered in patients with advanced AMD (Lanzl et al 2011). Based on these findings, one might hypothesize that also retinal blood flow regulation may be compromised in patients with AMD.…”
Section: Introductionmentioning
confidence: 99%
“…Retinal vessel response to drugs already used in ophthalmology has recently begun to draw interest (Papadopoulou et al. 2009; Lanzl et al. 2011).…”
Section: Discussionmentioning
confidence: 99%